PENGEMBANGAN MODUL AJAR BERBASIS ETNOMATEMATIKA PADA MATERI LINGKARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 2 GEGER - Adinda Putri Fajarsari; Ika Krisdiana; Titin Masfingatin (UPT Penerbitan Universitas Jember, 2022)
This development research aims to develop mathematics teaching materials in the form of learning modules on culturally based circle materials. Culture-based learning allows students and teachers to actively participate in the introduction of cultures they already know in order to improve student learning outcomes. One that can bridge between culture and mathematics is Ethnomathematics. The research method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMP Negeri 2 Geger. This research was used to determine the level of validity, practicality, and effectiveness of the teaching modules developed. The resulting product is in the form of an Ethnomathematics-based teaching module. The results showed that the combined score of two validators to determine the level of validity was 95.35% (very valid), and the results of the teaching module practicality test got a score with a final percentage of 79.60% (practical), an effectiveness test through a learning outcomes test with an average score of 85.06 with a percentage of completion of 90.62%. Based on the research conducted, it can be concluded that the development of ethnomathematics-based teaching modules on class VIII circle materials that are developed is valid, practical, and effective to improve student learning outcomes. Keywords: Modul Ajar, Matematika, Etnomatematika, Lingkaran.